Dire sans entraves ! - Jérémy Perrin (Flaubert: Revue Critique et Génétique)
Madame Bovary is the novel of failed dialogs: Flaubert’s mistrust of the spoken word is manifest in particular in the famous passage about the “cracked caldron”. This article explores the five varieties of ineffective speeches that reflect throughout the plot the low esteem in which language is held. It also shows how these speeches, by hinting at the alienation from society, herald certain structuralist and situationist themes in Flaubert.